2008
DOI: 10.1111/j.1471-4159.2008.05519.x
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin increases post‐ischemic damages in organotypic hippocampal slice cultures

Abstract: Clusterin or apolipoprotein J is a heterodimeric glycoprotein which is known to be increased during tissue involution in response to hormonal changes or injury and under circumstances leading to apoptosis. Previous studies in wild-type (WT) and clusterin-null (Clu-/-) mice indicated a protective role of clusterin over-expression in astrocytes lasting up to 90 days post-ischemia. However, in in vitro and in vivo models of neonatal hypoxia-ischemia, clusterin exacerbates necrotic cell death. We developed recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…Previous findings from animal studies suggested that Clusterin increases post-ischemic damage and may exert a negative effect on the structural integrity and functionality of hippocampal neurons. 44 Several limitations may be noted in this study. First, sample size (558 patients and 566 controls) might not be adequate.…”
Section: Discussionmentioning
confidence: 90%
“…Previous findings from animal studies suggested that Clusterin increases post-ischemic damage and may exert a negative effect on the structural integrity and functionality of hippocampal neurons. 44 Several limitations may be noted in this study. First, sample size (558 patients and 566 controls) might not be adequate.…”
Section: Discussionmentioning
confidence: 90%
“…While extracellular Zn 2+ via the ZnR is shown to promote cell survival, an opposing role is suggested for intracellular Zn 2+ rise that often leads to cell death [59], [60], [61], [62], [63]. Interestingly, upregulation of the pro-apoptotic nCLU form by ischemia, which is known to induce a rise in intracellular Zn 2+ , has been shown to play a role in neuronal death [64], [65]. Consistent with such a role, intracellular Zn 2+ or Cd 2+ rise induces expression of the pro-apoptotic nCLU and triggers testicular germ cells death [66].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the experimental conditions were different, as neonatal hypoxia/ischemia and permanent ischemia by middle cerebral artery occlusion in adult mice were used, respectively. CLU increases post-ischemic cell death in hippocampal slice cultures [42], implying a pro-apoptotic role for CLU.…”
Section: Clu In Brain Damage and Neurodegenerationmentioning
confidence: 99%